Making Migrants ‘Il-legible’: The Policies and Practices of Documentation in Post-Apartheid South Africa. - Amit, R.; Kriger, M. (My University, 2014)
In South Africa, the Department of Home Affairs (DHA) – the department charged with managing migration – has struggled to control growing migration flows, particularly the increased demand on the asylum system. The DHA has both relied on and sought to undermine documentation attempts as part of its migration management efforts. These shifting practices reveal an official ambivalence toward granting foreign migrants documents and the rights that accompany them. Ensuring that foreign migrants remain undocumented fulfils the DHA’s objective of facilitating their removal, but it undercuts the administration’s ability to know who is in the country, another expressed DHA goal. Examining two documentation schemes – the asylum system, and the three-month documentation programme targeting undocumented Zimbabweans – this article highlights these conflicting purposes. It explores the DHA’s administrative strategies and practices to withhold or deny documentation, and hence legal rights, to foreign migrants even when its stated goal is documentation. Looking at the role that documentation plays in state administration, the article argues that the street-level organisational approach and its focus on implementation best captures the actions of the DHA, underscoring the ways in which street-level bureaucrats can influence documentation policy and practice by determining who gets access to documents.
Keywords: migration flow; migration management; documentation programme; asylum system; document policy